Perceived Quality and Satisfaction in an Excellence Teacher Professional Ability Training Programme: Evidence from Primary and Secondary School Teachers in Chongqing - Li, Lebin (Quality in Sport, 2025)
Background: Excellence-oriented teacher professional development (PD) programmes have been promoted in China to support teachers in implementing curriculum reforms, promoting students’ physical and mental health and strengthening school physical education and health education. However, empirical evidence on how frontline teachers perceive the quality of such programmes, and which design features matter most for their overall satisfaction, remains limited. This study evaluates teachers’ perceptions of a provincial Excellence Teacher Professional Ability Training Programme in Chongqing, with particular attention to programme quality dimensions and primary–secondary stage comparisons. Material and methods: Data were collected via a post-training questionnaire from 48 in-service teachers (9 primary, 39 secondary) who participated in the programme. The instrument measured overall satisfaction, perceived programme organisation, content relevance, lecturer expertise, time allocation and interactive engagement, as well as satisfaction with specific course components (e.g. mental health education, classroom and crisis management, AI-era classroom design). Responses were given on five-point Likert scales. Descriptive statistics were used to characterise evaluation profiles; independent-samples t tests compared primary and secondary teachers; Pearson correlations examined associations between variables; and multiple linear regression identified predictors of overall satisfaction. Results: Teachers reported generally positive evaluations of the programme across all quality dimensions and course components. No statistically significant differences were found between primary and secondary teachers in overall satisfaction or dimension scores. Correlation analyses showed strong positive associations between overall satisfaction and perceived organisation, content relevance, lecturer expertise, time allocation and interactive engagement. The regression model was significant, F(4, 43) = 19.37, p < .001, explaining 64.3% of the variance in overall satisfaction. Content relevance emerged as the only significant unique predictor, while other dimensions did not retain independent effects when entered simultaneously. Conclusions: The findings suggest that excellence-oriented PD programmes can be well received by teachers across school stages when basic organisational conditions and interaction opportunities are met. Content that closely matches teachers’ real classroom challenges, curriculum demands and health-oriented reform tasks appears particularly critical for driving overall satisfaction. For the design of future programmes in school physical education and health education, prioritising high-relevance, practice-based content may be more consequential than further refinements in scheduling or delivery format alone.